Migration patterns and habitat use by molt migrant temperate‐breeding Canada geese in James Bay, Canada. Issue 1 (9th November 2022) - Sorais, Manon; Patenaude‐Monette, Martin; Sharp, Christopher; Askren, Ryan; LaRocque, Armand; Leblon, Brigitte; Giroux, Jean‐François
Abstract : Numbers of temperate‐breeding Atlantic and Mississippi Flyway Canada geese have greatly increased since the 1980s. Consequently, numbers of yearlings, sub‐adults and failed breeders undertaking pre‐molt migration to northern latitudes has also increased, potentially providing additional hunting opportunities for Cree hunters living near James Bay, Canada. We described movement patterns and habitat use of molt migrant Canada geese Brenta canadensis maxima along the east coast of James Bay based on nine geese fitted with GSM–GPS devices during 11 northward and eight southward migrations between 2015 and 2019. Geese staged for 2.8 ± 0.6 days (mean ± standard error of the mean) at 3.2 ± 0.6 staging sites (mostly tidal flats and salt marshes) from the first week of June in spring and 3.8 ± 1.8 days at 2.0 ± 0.5 staging sites (mostly inland freshwater wetlands, peatlands and tidal flats) from the first week of September when returning south. Shallow and deep water habitats were used as resting sites during both migrations. In spring, molt migrants were mostly harvested in June well after the migration of sub‐arctic breeding geese whereas in autumn, both subspecies were harvested in September. Molt migrant temperate‐breeding geese can increase harvest opportunities and represent supplementary wildlife food for Cree communities. However, the current number of molt migrant geese harvested by Cree hunters is not sufficient to significantly impact populations of temperate‐breeding geese.